1998
DOI: 10.1017/s003329179800659x
|View full text |Cite
|
Sign up to set email alerts
|

Response of hostile individuals to stressful change in their working lives: test of a psychosocial vulnerability model

Abstract: Background. According to the psychosocial vulnerability model, the health of hostile individuals is at greater risk than that of non-hostile individuals, due partly to lesser ability of the former to cope with psychosocial stress situations. We examined whether hostile individuals were more vulnerable than others to health problems when faced with stressful changes in their working lives. Methods. Hostility, sickness absence and psychosocial stressors in 866 local government employees over a 5-year period, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…Work-family balance and relationship effects and links to burnout, as well as age-related effects, are also attracting increased attention. Existing studies have pointed to both gender and age differences in terms of the impact of downsizing (36,61). A Swedish study (54) of repeated downsizing in the retailing industry found that older workers were more likely to experience adverse effects and long-term symptoms of distress.…”
Section: Review Of Findings and Discussionmentioning
confidence: 99%
“…Work-family balance and relationship effects and links to burnout, as well as age-related effects, are also attracting increased attention. Existing studies have pointed to both gender and age differences in terms of the impact of downsizing (36,61). A Swedish study (54) of repeated downsizing in the retailing industry found that older workers were more likely to experience adverse effects and long-term symptoms of distress.…”
Section: Review Of Findings and Discussionmentioning
confidence: 99%
“…Absence may reflect distal risk factors for mortality. For example, a hostile personality and work stress are predictors of premature death in initially healthy populations,20 21 and sickness absence is associated with these factors 22…”
Section: Discussionmentioning
confidence: 99%
“…A limitation in our analyses is that other potentially important covariates shown in the directed acyclic graph (DAG) (www.sjweh.fi/index. php?page=data-repository) were not available, such as personality, spouse work status, household income and organizational changes at the workplace, which may be associated with informal caregiving, job strain and sickness absence (66,67). However, household income is highly associated with being married and occupational grade (for which we adjusted), and the association between spouse work status and long-term sickness absence is likely to go through household income.…”
Section: Mortensen Et Almentioning
confidence: 99%